A model for research on film-induced tourism: Audiovisual narrative texts, reception, and effects - Jorge Nieto-Ferrando; Beatriz Gómez-Morales; Sebastián Sánchez-Castillo (Annals of Tourism Research Empirical Insights)
Studies of film-induced tourism have demonstrated the effect of film and television productions on tourist attitudes and experiences. However, most of these studies focus on effects without considering the content or reception of film texts. With a view to filling this gap, this study proposes a model based on the analysis of film texts and text reception. The model is tested using the film Zindagi na milegi dobara and its reviews on IMDb. The results of the study confirm the inextricable connections between the representation of tourist attractions, the way viewers interact with the film, and the effects on tourist destination recall.